Thriving in Transition: Unpacking the Keys to Expat Retention in Vietnam’s Higher Education Landscape - Arokiasamy, Anantha Raj A.; Zouba, Mohamed Abderrahim; Thet, Khine Zar Zar; Vasudevan, Asokan; Hossain, Syed Far Abid; Al-Hunaiyyan, Ahmed (Journal of Cultural Analysis and Social Change, 2026)
Expatriate retention is a key concern in international human resource management, especially in emerging economies like Vietnam. In higher education, where foreign academic talent is essential, understanding factors that support expatriate success is critical. Prior studies indicate that perceived organizational support (POS) facilitates adjustment and retention. Additionally, self-regulation is the ability to manage one’s own behavior and performance may influence how well expatriates adapt and remain committed. This study investigates the relationships among perceived organizational support, job adjustment, and expatriate retention in Vietnam's higher education sector. It also examines the mediating role of job adjustment and the moderating role of self-regulation. The research presents a novel framework relevant to institutional policy and expatriate management in Vietnam. A quantitative, explanatory design was employed. Using simple random sampling, data were collected from 357 expatriates working in higher education institutions in Vietnam. Data analysis involved regression, moderated multiple regression, and Partial Least Squares Structural Equation Modeling (PLS-SEM) to test the conceptual model. Perceived organizational support significantly enhances job adjustment, which in turn positively affects expatriate retention. Job adjustment mediates the relationship between organizational support and retention. Self-regulation, especially in planning and performance moderates the effect of job adjustment on retention, highlighting the importance of both organizational and individual factors. This study underscores the value of organizational support and self-regulation in enhancing expatriate adjustment and retention. It is one of the first to test this model in Vietnam’s higher education context. Institutions should support proactive behavior and cultural preparedness to improve expatriate experience and retention in emerging markets.